Kajian Eksitensi Spasial Dalam Pemberdayaan Nilai-Nilai Arsitektural umah jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Teknik Mesin Fak. Teknik UGM, 2003)
When someone talks about architecture at the same time they asked to connect architecture to the general the architectural studies should be encourage to the concept, construction method and the culture". In real condition of buildings and it's surrounded